Analysis of E-mail Transactions in Virtual Reference Services - Nur Qomariyah, Astutik; Dwi Kusuma, Rusdiyah Ciptaning (D3 Teknisi Perpustakaan Fakultas Vokasi Universitas Airlangga, 2015)
Today, the use of traditional reference desk in the academic libraries has been rarely used, thus expanding or even move to a virtual reference service. A minimum level of virtual reference services are provided in the academic library is currently in general is the electronic mail (e-mail). One of the academic library specifically provide virtual reference services via e-mail is a Petra Christian University (PCU) Library (refdesk@petra.ac.id.). In such services librarians provide assistance to users in finding information and answer questions. This study aimed to analyze the transaction reference services virtually through e-mail at the PCU Library, with a view of the types of questions based on user background, the writing style of language communication interaction used based on user background, and cultural values are revealed behind the user in virtual reference services (e-mail). This study uses content analysis (content analysis) of the transcript e-mail received librarians of reference services began March 10 until June 16, 2015. The results showed that the types of questions asked in reference service virtual (e-mail) in the Library UK Petra include: specific search, access online resources, operation of online resources, policies and procedures for services, and library holdings with background the student (PCU and non-PCU), faculty, and librarians. Based on the background of users found that overall more types of questions asked in virtual reference services (e-mail) is a problem of access to online resources, and generally submitted by the students. Then, the writing style of the users language in interaction reference service virtual (e-mail) tends to be formal, which includes the word greeting, the message will be delivered, and regards cover, either by the student (PCU and non-PCU), lecturer, or librarians. While cultural values that revealed the background behind the user in virtual reference services (e-mail) is obedience, courtesy and politeness users. Keywords: virtual reference services, e-mail reference service, e-mail transactions, content analysis, academic libraries